Analisis Kemampuan Pemecahan Masalah Matematis ditinjau dari Kepercayaan Diri Siswa SD Kelas V - Rustam, Ahmad; Arif; Husain, Itsnain Alfajri; Iriyadi, Deni; Sari, Wiwin Rita (Arus Jurnal Pendidikan, 2023)
This study aims to describe and analyze mathematical problem solving abilities in terms of students' self-confidence. The research was carried out in the odd semester of the 2022/2023 academic year around October 2022, with 14 research subjects. The results of this study were: (1) 21.43% had high self-confidence, 28.57% had moderate self-confidence, 35.71% had low self-confidence, and 14.29% had very low self-confidence, (2) 21.43% had mathematical problem solving abilities capable category, 28.57% have enough ability, 35.71% less category, and 14.29% very less category, (3) A total of 3 students have high self-confidence and are able to solve mathematical problems. As many as 4 students have moderate self-confidence, quite capable of solving mathematical problems. As many as 5 students have low self-confidence, are unable to solve mathematical problems, and 2 students have very low self-confidence and are very less able to solve mathematical problems. The conclusion of this study is that the self-confidence and problem solving abilities of fifth grade students at SD Negeri 53 Waemputang are still in the low category. Students who have high self-confidence have the ability to solve mathematical problems, and vice versa students who have low self-confidence tend to have less ability to solve mathematical problems. Between problem solving abilities and students' self-confidence has linearity or is directly proportional.